Synesthesia : perspectives from cognitive neuroscience - Robertson, Lynn C.; Sagiv, Noam (Oxford University Press, 2005)
Owing to its bizarre nature and its implications for understanding how brains work, synesthesia has received a lot of attention in the popular press and motivated a great deal of research and discussion among scientists. The questions generated by these two communities are intriguing. This volume aims to provide answers to these questions.